User Experience Analysis on SSO Portal - Wira Darma, I Gede; Sri Utami, Komang; Sudarma, Made (International Journal of Engineering and Emerging Technology; Vol 3 No 2 (2018): July - December, 2019)
The need for data and information access makes a college build or use an information system to support their operational activities. Users will feel very helpful if the existing system can help their work, taking into aspects of user experience can help in achieving this. The experience of users using the system needs to be studied to determine the level of user satisfaction with the system that has been developed. The main purpose of this study is to assess aspects of user experience in terms of usability. The usefulness of the aspects measured includes effectiveness, efficiency, learning ability and satisfaction. Effectiveness is measured using the first click testing technique and calculating errors during the usability test process. Efficiency is calculated by finding the time needed to complete the task. User measured satisfaction with the system was measured using the SUS questionnaire. SEQ is used to measure the level of difficulty of tasks or scenarios given during the test. Based on the assessment of the respondents, usability aspects of the system have been achieved, but there are additional things that must be addressed related to system design to improve the usability aspect.